MODEL KOMUNIKASI TERAPIS ANAK AUTIS DI SLB AUTISMA MUTIARA BANGSA PRATAMA PADANG - Elvi Safri Dinyyati Rahmatika; Neni Efrita (Al Irsyad : Jurnal Bimbingan Konseling Islam, 2018)
Autisma Mutiara Bangsa Pratama SLB Padang is one of the educational institutions that provide treatment for children with special needs, people with autism. Autistic children are a group of children experiencing communication disorders, and have behavioral abnormalities that cause children to be only interested in their own mental activities. For this reason a therapist is needed to play a role in dealing with autistic children, as an effort to develop character and personality through interactional and transactional communication models. This study uses a qualitative method with a descriptive approach. The tool for collecting research data is through observation, interviews and documentation. with the determination of informants by purposive sampling technique. The results of the study explain the interaction therapist model of autistic child therapists, namely the therapist interacts with the child's feeling of comfort, so that the child focuses when the communication process takes place. By way of greeting when coming to school, during class hours, and during breaks. To be able to follow the therapist's commands such as equalizing, pointing and mentioning images of objects, fruits, animals and so on both verbally and non-verbally. Whereas the transactional communication model of an autistic child therapist is that the therapist stimulates the child to complete several stages such as the name recognition stage, questioning and self-attendance. This is done based on identification such as fine and rough motor identification, simple words, vocals, images, limbs and also academic identification.